Evolutionary scenarios for the emergence of recursion - Barceló-Coblijn, Lluís (Theoria et Historia Scientiarum, 2012)
As we have seen, the evolution of language cannot be addressed from the perspective of a single discipline; others, such as genetics or archaeology, also have a say on this issue. There is still a lot of research needed regarding Neanderthal cognition, an issue that deserves more attention also by biolinguistics. Although there are reasons to think so, the available data do not allow us to exclude recursion either from the cognition of H. neanderthalensis or starlings. Thus, what can be called special in humans or in language? The last part of the next quotation may summarize almost perfectly our own hypothesis about the role of recursion in language and in the whole cerebral architecture related to linguistic and non-linguistic activity.